The nutty professor - Grazer, Brian; Shadyac, Tom (USA: Universal Home Video [production company] ; Kuala Lumpur : Berjaya HVN Sdn. Bhd. [distributor], 1998)
Dr. Sherman Klump, a kind,'calorically challenged' genetics professor who longs to shed his 400 pound frame in order to win the heart to beautiful Jada Pinkett
Cast: Eddie Murphy, James Coburn, Larry Miller, Dave Chappelle, John Ales